2001
DOI: 10.1007/s004390100501
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional characterisation of mild MCAD deficiency

Abstract: Molecular and functional characterisation of mild MCAD deficiencyZschocke, J.; Schulze, A.; Lindner, M.; Fiesel, S.; Olgemöller, K.; Hoffmann, G.F.; Penzien, J.; Ruiter, J.P.N.; Wanders, R.J.A.; Mayatepek, E. General rights It is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
41
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 11 publications
7
41
1
Order By: Relevance
“…This mutation has never been identified in patients with a clinical phenotype, but in several newborns identified by neonatal screening in the United States, Australia, and Germany Smith et al 2010;Zschocke et al 2001). These newborns had a relatively mild acylcarnitine profile, like our patient 8, that was compound heterozygous for this and for the common mutation and only presented a slight elevation of metabolites.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This mutation has never been identified in patients with a clinical phenotype, but in several newborns identified by neonatal screening in the United States, Australia, and Germany Smith et al 2010;Zschocke et al 2001). These newborns had a relatively mild acylcarnitine profile, like our patient 8, that was compound heterozygous for this and for the common mutation and only presented a slight elevation of metabolites.…”
Section: Discussionmentioning
confidence: 56%
“…The c.799G>A (p.G267R) mutation has been previously reported in symptomatic patients (Yokota et al 1991;Andresen et al 1997;Zschocke et al 2001). Glycine 267 is highly conserved in humans and other organisms and are found at the equivalent positions in human short-chain and branched-chain acylCoA dehydrogenases (Zschocke et al 2001). Expression studies in Escherichia coli revealed a decrease of the enzyme activity that could be increased by co-overexpression of the GroESL chaperonins (Andresen et al 1997).…”
Section: Discussionmentioning
confidence: 96%
“…All exons and parts of the neighbouring intron regions of the ACADM gene (NM_000016.4) were analysed by direct sequencing (Zschocke et al 2001). Mutations are described according to the recommendations of HGVS (http://www.hgvs.org/ mutnomen/).…”
Section: Genotypementioning
confidence: 99%
“…Both our patients carried a known disease-causing mutation on the second allele (patient 17 c.199T>C and c.799G>A; patient 21 c.199T>C and c.985A>G). The mutation c.799G>A has been found in patients detected asymptomatically by newborn screening (Zschocke et al 2001), as well as in symptomatic patients (Yokota et al 1991;Andresen et al 1997). This mutation has been classified as severe (Smith et al 2010;Sturm et al 2012).…”
Section: Clinical Phenotypementioning
confidence: 99%
“…Classical OAD, such as methylmalonic aciduria (MMA), propionic aciduria (PA), and isovaleric aciduria (IVA), characteristically present with metabolic acidosis, hypoglycemia, hyperketosis, elevated lactate, and hyperammonia during catabolic state, whereas cerebral OAD, such as glutaric aciduria type I (GA-I), predominantly exhibit neurologic symptoms (dystonia, ataxia, encephalopathy, seizures) (2,10,11,13-16,18 -21). At present, genotype phenotype correlation in the majority of these diseases is poorly understood and remarkable variations in the disease course have been described, ranging from asymptomatic patients to fatal course after neonatal onset (10,15,(22)(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%